The Challenge Face in the Implementation of Competency-Based Curriculum in Northern Kenya - Hussein, Adan (African Journal of Education and Practice, 2023)
Purpose: Kenya is in the process of changing its educational system from one that is content-based to one that is competency-based. When implementing a new curriculum, teachers are likely to encounter difficulties, particularly with regard to the divisions of material and subjects, underlying presumptions, objectives, teaching strategies, and assessment techniques. In this regard, this study aimed to look into the challenges that northern Kenya had in implementing the competency-based curriculum successfully. The study's particular goals were to: Analyze the potential of the competency-based curriculum (CBC) and its effects on the stability of the education sector in northern Kenya, which will depend on the infrastructure available for its implementation; the results of this assessment will assist the government in implementing the competency-based curriculum. The 8-4-4 curriculum which is planned to be replaced by CBC had been implemented mostly by applying the transmission approach and children were reported to be attending primary school and not learning (KNEC, 2010 & UWEZO, 2013). Methodology: The study employed a descriptive research design. Simple random sampling was employed. The study had a sample size of 45 primary school teachers and 15 head teachers. A questionnaire and interview schedules were used to collect data from the respondents. Findings: Teacher quality determines the quality of curriculum implementation and one means of ensuring teacher quality is by making continuing teacher professional development available for teachers. The country should take into consideration teacher preparedness for the implementation of the new curriculum and whether the country is fully prepared to organize a teacher professional development program for sustained teacher quality. Unique Contribution to Theory, Practice and Policy: The study's foundation was Dewey's Social Constructivism Theory, which highlights how interaction and experience are the fundamental building blocks of human experience. The study suggests that in order to foster a positive attitude among teachers and successfully implement a competency-based curriculum, the Ministry of Education should increase its investment in teacher training and involve them in the curriculum change process. The study established that there was little extent of parental involvement in curriculum implementation in schools. Similarly, Sifuna and Obonyo (2019) examined the challenges hindering the effective implementation of CBC in Kenya. The study highlighted that there was an inadequacy of instructional materials and a lack of participation by parents in the curriculum implementation process.